Carbon Reduction Powered by Natural Electrochemical Gradients under Submarine Hydrothermal Vent Conditions - T. Altair; E. Dragoti; V. Sojo; Y. Li; S. Skiffington; W.A. Sullivan; G.T. Drozd; S.E. McGlynn; D. Galante; H. Varela; R. Hudson (Journal of the American Chemical Society, 2025)
Abstract Energy metabolism at the emergence of life has been the topic of intense theoretical and experimental study. Alkaline hydrothermal vents (AHVs) may have facilitated energy transfer and carbon fixation at life’s emergence. Specifically, pH separation across vent walls could have been the forerunner to pH separation across cell membranes, with inorganic barriers containing [Ni-]FeS minerals as precursors of metalloenzymes in potentially ancient biological reductive acetyl-CoA Wood–Ljungdahl (WL) and other metabolic pathways. We previously demonstrated pH-gradient-dependent reduction of CO2 to formate by H2 in AHV interface conditions. Here, we address the same problem of CO2 reduction using a macroscale reactor with minerals synthesized via protocols meant to mimic the natural processes of hydrothermal chimney formation. This reactor also allowed us to probe more variables and explore longer experimentation time frames. These results elucidate how different aspects of the hydrothermal–vent interface (e.g., different minerals and/or temperature gradients) affect the observed CO2 electrochemical reduction as well as the flow of electrons under passive vs induced currents and potentials. Using experimental simulations and electrochemistry techniques, we detected two key steps of the WL pathway (CO2 to formic acid and the formation of acetic acid). We explored effects of Ni incorporation in the mineral catalyst, as well as temperature and the effects of these variables on the production of formate. Currents as small as 10 nanoamps to 10 microamps were enough to efficiently carry out CO2 reduction. In this work, we electrochemically explore energy protometabolism in vent–ocean interfaces, specifically focusing on [Ni-]FeS minerals as precursors of metalloenzymes.